2017
DOI: 10.3390/molecules22071214
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weights of Bovine and Porcine Heparin Samples: Comparison of Chromatographic Methods and Results of a Collaborative Survey

Abstract: In a collaborative study involving six laboratories in the USA, Europe, and India the molecular weight distributions of a panel of heparin sodium samples were determined, in order to compare heparin sodium of bovine intestinal origin with that of bovine lung and porcine intestinal origin. Porcine samples met the current criteria as laid out in the USP Heparin Sodium monograph. Bovine lung heparin samples had consistently lower average molecular weights. Bovine intestinal heparin was variable in molecular weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
(13 reference statements)
0
17
0
Order By: Relevance
“…[4][5][6][7] Improvements in analytical approaches for evaluation of heparins (e.g. two-dimensional [2D] nuclear magnetic resonance [NMR] and anti-FIIa and -FXa chromogenic assays) have demonstrated that UFH preparations from distinct animal sources may have different molecular size, disaccharide compositions, anticoagulant/anti-thrombotic potencies and/or homogeneities (mixture of distinct UFH chains), [7][8][9][10][11][12][13][14] as shown in ►Fig. 1A, B and ►Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Improvements in analytical approaches for evaluation of heparins (e.g. two-dimensional [2D] nuclear magnetic resonance [NMR] and anti-FIIa and -FXa chromogenic assays) have demonstrated that UFH preparations from distinct animal sources may have different molecular size, disaccharide compositions, anticoagulant/anti-thrombotic potencies and/or homogeneities (mixture of distinct UFH chains), [7][8][9][10][11][12][13][14] as shown in ►Fig. 1A, B and ►Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is the most preferred material for the innovation of light, and thin-film solar cells. These batteries have tape holes that can absorb light more efficiently and increase their efficiency [26]. During the initial assembly of these solar cells, the CdTe -based solar cells are made of polyglass-like materials, and glass is selected as the substrate.…”
Section: Cadmium Telluride Thin Film Solar Cell (Cdtc)mentioning
confidence: 99%
“…The underlying structure of heparin is known to be tissue specific and differs between species, with individual animals of the same species exhibiting differences. Such variations are observed throughout the molecular weight populations, disaccharide compositions, and anticoagulant activities (Table 1, Figure 2A) [1,10,13,14,15]…”
Section: Heparin Structurementioning
confidence: 99%
“…MW has also been defined using 13 C NMR [101] and MS [102,103] . Size definition when compared to standards is difficult, as standards are hard to define or acquire, meaning that they are usually created in-house, leading to variation between labs, however a USP MW standard is available to try to reduce this [6,14,94]. A triple detector (TDA) approach has also been utilised, where a RALS detector, a differential refractive index detector (SLS detection), and a viscometer are used in concert to accurately define the MW of heparin and may also be used to create uniform standards [104].…”
Section: Alternative Techniques That May Assist In Heparin Qualitymentioning
confidence: 99%